Biochemical diversity of glycosphingolipid biosynthesis as a driver of Coccolithovirus competitive ecology. (20th May 2019) - Nissimov, Jozef I.; Talmy, David; Haramaty, Liti; Fredricks, Helen F.; Zelzion, Ehud; Knowles, Ben; Eren, A. Murat; Vandzura, Rebecca; Laber, Christien P.; Schieler, Brittany M.; Johns, Christopher T.; More, Kuldeep D.; et al.
Summary: Coccolithoviruses (EhVs) are large, double‐stranded DNA‐containing viruses that infect the single‐celled, marine coccolithophore Emiliania huxleyi . Given the cosmopolitan nature and global importance of E. huxleyi as a bloom‐forming, calcifying, photoautotroph, E. huxleyi –EhV interactions play a key role in oceanic carbon biogeochemistry. Virally‐encoded glycosphingolipids (vGSLs) are virulence factors that are produced by the activity of virus‐encoded serine palmitoyltransferase (SPT). Here, we characterize the dynamics, diversity and catalytic production of vGSLs in an array of EhV strains in relation to their SPT sequence composition and explore the hypothesis that they are a determinant of infectivity and host demise. vGSL production and diversity was positively correlated with increased virulence, virus replication rate and lytic infection dynamics in laboratory experiments, but they do not explain the success of less‐virulent EhVs in natural EhV communities. The majority of EhV‐derived SPT amplicon sequences associated with infected cells in the North Atlantic derived from slower infecting, less virulent EhVs. Our lab‐, field‐ and mathematical model‐based data and simulations support ecological scenarios whereby slow‐infecting, less‐virulent EhVs successfully compete in North Atlantic populations of E. huxleyi, through either the preferential removal of fast‐infecting, virulent EhVs during active infection or by having access to a broader host range.